Malignancy rates in patients with rheumatoid arthritis treated with tocilizumab. Issue 1 (10th May 2016) - Rubbert-Roth, Andrea; Sebba, Anthony; Brockwell, Laura; Kelman, Ariella; Porter-Brown, Benjamin; Pulley, Jennifer; Napalkov, Pavel; van Vollenhoven, Ronald F
Abstract : Objective: To analyse malignancy rates in patients with rheumatoid arthritis (RA) treated with tocilizumab. Methods: Patients who received tocilizumab or placebo+methotrexate/disease-modifying antirheumatic drugs in the double-blind phases of 5-phase three trials or who received at least 1 dose of tocilizumab in the long-term extension studies were analysed up to the 2 May 2012 cut-off date. Malignancies were monitored throughout the studies, analysed and adjudicated as malignant by medical review. Risk was compared with that in the general population using standardised incidence ratios (SIRs) based on data from the Surveillance Epidemiology and End Results SEER (US general population) and GLOBOCAN (non-US general population) databases. Results: In total, 4009 patients in the tocilizumab all-exposure population were included. Mean treatment duration was 4.0 years (mean 5.1 (range 0.0–6.8); total observation time was 16 120.1 patient-years (PY). The adjudicated malignancy rate (95% CI) was 1.26/100 PY (1.09 to 1.44) and remained constant over time. The SIR (95% CI) for all malignancies combined, excluding non-melanoma skin cancer, was 1.36 (1.01 to 1.80) for US and 1.81 (1.44 to 2.23) for non-US populations, driven primarily by higher rates in lung and bronchus (US/non-US) malignancies and prostate cancer and non-Hodgkin lymphoma (non-US), in contrast to those for the general populations; these higher rates are in line with those expected in patients with RA or in the geographic regions studied. Conclusions: Malignancy rates remained stable with long-term tocilizumab treatment, and malignancy types and rates were consistent with those expected in patients with RA.